Prevalence rate of gastrointestinal nematodes and total worm count in sheep - Ramli, Nur Syairah (2015)
The prevalence of gastrointestinal (GI) nematode parasites was determined in 50 sheep raised in a smallholder farm in Salak Tinggi, Selangor. The sheep comprised of 27 Damara crosses and 23 Barbados Blackbelly crosses grouped into two age groups: young and adult. Faecal samples were examined for strongyle nematode egg count as egg per gram (EPG) using modified McMaster technique. Severity of infection was categorized into mild, moderate and heavy based on EPG. Five sheep were randomly slaughtered for adult GI nematodes identification by total worm count (TWC) method. FAMACHA score was used for investigation of worm load based on anaemic condition. The study revealed the prevalence rate of EPG was 88%, of which 84.1% of the sheep had mild infection. Barbados Blackbelly crosses were significantly different (p=0.002) in EPG prevalence rate compared to Damara crosses. There was significant difference (p=0.004) in EPG between age groups for Barbados Blackbelly crosses but not for Damara crosses (p=0.941). Correlation between severity of infection and FAMACHA score was significant (r=0.289; p=0.042). From TWC, Haemonchus was the most predominant nematode followed by Trichostrongylus and Oesophagostomum. EPG and TWC for Haemonchus was positively correlated but not significant (r=0.85, p=0.066). From regression analysis, 73% of the variability in TWC for Haemonchus could be explained by EPG. Thus it can be concluded that FAMACHA score correlates well with severity of infection of nematode and can be used to assess the strongyle nematode burden in sheep.